MARKETING STRATEGIES TO INCREASE THE COMPETITIVENESS OF SMALL AND MEDIUM BUSINESS (Marketing Journal, 2024)
The article highlights the importance of using innovative marketing strategies of small business entities producing industrial products. He studies the theoretical aspects of the management of the market activity of small industrial enterprises and the introduction of innovations into the production process. Innovative marketing strategies aimed at increasing the competitiveness of small business entities will be systematized.